"Integration of the content of education as a means of training a competent specialist". - Bozhko, N. V. (Problems of Engineer-Pedagogical Education, 2018)
The article examines the competence approach to training qualified workers in the system of vocational education of Ukraine and providing future specialists with integrated knowledge. The paper considers the implementation of the State Standards of Vocational Education of the "first" and "second" generation into the educational process, analyzes the structure of the State Standard of Vocational Education based on the competence approach, and provides definitions of some relevant concepts such as professional competences (basic and specialized), key competences, training module, and basic unit. The author of the present article gives explanations concerning the lexical meaning of the words "integrating", "integrative", "integrated", and "integral". The terms "integral competence" and "integrated competence" are considered in detail. Structural components of the integrated competence and the methodological foundations for its formation are analyzed. The development of the integrated competence of future specialists is viewed considering the example of training qualified workers for the garment industry in the system of vocational education of Ukraine.